2021
DOI: 10.1021/acs.jpca.1c06465
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Volatile Organic Compound (AVOC) Autoxidation as a Source of Highly Oxygenated Organic Molecules (HOM)

Abstract: Gas-phase hydrocarbon autoxidation is a rapid pathway for the production of in situ aerosol precursor compounds. It is a highway to molecular growth and lowering of vapor pressure, and it produces hydrogen-bonding functional groups that allow a molecule to bind into a substrate. It is the crucial process in the formation and growth of atmospheric secondary organic aerosol (SOA). Recently, the rapid gas-phase autoxidation of several volatile organic compounds (VOC) has been shown to yield highly oxygenated orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 94 publications
2
22
0
Order By: Relevance
“…For the time being, HOM analytics mainly rely on MS methods where they are analyzed from the gas phase since the reactivity of their supposed peroxide groups makes them unstable and causes analytical problems. 73,76 Peroxide compounds are challenging as they may degrade in SOAs within a few hours. 127 Analytics are also limited because the exact structures of HOM compounds are still unknown.…”
Section: Analytical Methods For Oxidized Compounds In the Atmospherementioning
confidence: 99%
See 3 more Smart Citations
“…For the time being, HOM analytics mainly rely on MS methods where they are analyzed from the gas phase since the reactivity of their supposed peroxide groups makes them unstable and causes analytical problems. 73,76 Peroxide compounds are challenging as they may degrade in SOAs within a few hours. 127 Analytics are also limited because the exact structures of HOM compounds are still unknown.…”
Section: Analytical Methods For Oxidized Compounds In the Atmospherementioning
confidence: 99%
“…127 Analytics are also limited because the exact structures of HOM compounds are still unknown. 76 Mutzel et al 72 have shown by LC-MS, employing DNPH derivatization, that HOMs found in the gas phase occurred also in the particle phase, and they contained carbonyl groups. Zhao et al 128 applied iodometry (discussed later) to LC-ESI-MS, in which samples were qualitatively analyzed for peroxide functionalities containing species before and after iodometry.…”
Section: Analytical Methods For Oxidized Compounds In the Atmospherementioning
confidence: 99%
See 2 more Smart Citations
“…This pathway produces hydrogen-bonding functional groups that allow a molecule to bind into a substrate. As stated by Rissanen [ 155 ], it is the crucial process in the formation and growth of atmospheric SOA.…”
Section: Scientific Backgroundmentioning
confidence: 99%